Leveraging natural killer cells for cancer immunotherapy. (May 2017) - Grossenbacher, Steven K; Aguilar, Ethan G; Murphy, William J
Natural killer (NK) cells are potent antitumor effector cells of the innate immune system. Based on their ability to eradicate tumors in vitro and in animal models, significant enthusiasm surrounds the prospect of leveraging human NK cells as vehicles for cancer immunotherapy. While interest in manipulating the effector functions of NK cells has existed for over 30 years, there is renewed optimism for this approach today. Although T cells receive much of the clinical and preclinical attention when it comes to cancer immunotherapy, new strategies are utilizing adoptive NK-cell immunotherapy and monoclonal antibodies and engineered molecules which have been developed to specifically activate NK cells against tumors. Despite the numerous challenges associated with the preclinical and clinical development of NK cell-based therapies for cancer, NK cells possess many unique immunological properties and hold the potential to provide an effective means for cancer immunotherapy.